2014
DOI: 10.4028/www.scientific.net/amm.660.60
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Laser Cutting Parameters on the Laminated Carbon Fibre Reinforced Plastics (CFRP) Composites Using DOE Technique

Abstract: Nowadays, carbon fiber reinforced plastics (CFRP) composites is widely used in the aerospace industry due to its excellent mechanical properties. In laser cutting process, high powers are used to cut materials then material melts and burns leaving edges with a high quality finish. To fulfill the high demand of cutting quality, a set of laser cutting parameters of CFRP material are studied. The objective of this experiment is to obtain an optimum laser cutting parameter thus minimizing the cutting defects parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The results clearly showed that the orientation of the fiber had an important influence on HAZ and surface roughness and +45°/−45° gave the better results than the other ways of orientation. On the other hand the study conducted by Wahab et al [ 75 ] did not show a clear influence of other input parameters such as cutting speed, gas pressure, and laser power, however, the kerf width was influenced negatively with higher values of cutting speed and laser power.…”
Section: Cutting Processes Of Natural Fiber-reinforced Polymer Commentioning
confidence: 76%
“…The results clearly showed that the orientation of the fiber had an important influence on HAZ and surface roughness and +45°/−45° gave the better results than the other ways of orientation. On the other hand the study conducted by Wahab et al [ 75 ] did not show a clear influence of other input parameters such as cutting speed, gas pressure, and laser power, however, the kerf width was influenced negatively with higher values of cutting speed and laser power.…”
Section: Cutting Processes Of Natural Fiber-reinforced Polymer Commentioning
confidence: 76%